Pengaruh Manajemen Mutu terhadap Kompetensi Pedagogik Guru di SMP Unggulan Mukhtar Syafa’at Blokagung Banyuwangi - Mahbub Mahbub; Bambang Sugiarto (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The objectives of this study are 1). to find out mutuyang management in SMP Unggulan Mukhtar Syafa'at Blokagung Banyuwangi, 2). to find out the pedagogical competence of teachers in SMP Unggulan Mukhtar Syafa'at Blokagung Banyuwangi, 3). to determine the effect of quality management on the pedagogical competence of teachers in SMP Unggulan Mukhtar Syafa'at Blokagung Banyuwangi. This research used quantitative descriptive method with product moment technique in data validity test and to find data reliability using alpha formula, while in hypothesis testing using F test and T test then for data analysis technique using normality test using regression model. Based on the results of research that has been done, the quality management managed by the institution can be said to be good. The pedagogical competence of the teachers at Mukhtar Syaudang Superior Junior High School was classified as good with a score percentage of 61% - 80%, meaning that the teacher's pedagogical competence was good. Then quality management greatly affects the pedagogical competence of teachers, which is 70.2% and 29.8% is influenced by other variables, so it is hoped that further researchers will conduct research related to the same theme, namely quality management with different indicators, in order to reveal 29.8. % other variables that affect teacher pedagogical competence.